The Influence of Marketing Management Learning and Self-Efficacy on Students' Entrepreneurial Intentions - Budi Jaya Sugiarto; Ony Kurniawati; Wahid Hidayat (Universitas Trunodjoyo Madura, 2026)
The intention to be entrepreneurial among college students is vital for developing graduates who can create jobs. Nonetheless, a lack of interest in entrepreneurship shows that just having academic knowledge isn't enough to promote entrepreneurial actions. This research aimed to investigate the combined impact of learning about marketing management and self-confidence on students' entrepreneurial intentions at WR Supratman University Method. A quantitative method using a causal associative framework was applied. The study sample included 30 learners from the Marketing Management Learning class, chosen through purposive sampling. Data were gathered using a five-point Likert scale questionnaire and were analyzed through multiple linear regression. Result. Results indicated that the regression analysis satisfied the classical criteria, with data showing normal distribution (Asymp. Sig. = 0.200). Tests conducted simultaneously demonstrated that learning marketing management and self-confidence had a significant effect on entrepreneurial intention (F = 3.715; p = 0.038), with a determination coefficient of 21.6%.Conclusion. Both marketing management learning and self-confidence collectively enhance students' entrepreneurial intentions. Universities should consider combining practical business education with initiatives that boost students' self-efficacy, thereby better preparing them as entrepreneurial graduates.